Responses and Challenges of Indonesian Prospective Elementary Teachers Interacting with Australian Avatar Students - Solihin, Annas; Mariana, Neni; Ledger, Susan; Fiscetti, John; Rappa, Natasha Anne (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The quality of teaching is a critical factor in educational success, and innovative tools like SimLab offer promising opportunities for enhancement. This research aims to analyze how SimLab user responses contribute to the development of teaching skills among students and to identify the challenges encountered during its implementation. A mixed-methods approach was employed, involving bilingual PGSD students from Unesa as the subjects of the study. Data were collected through a combination of surveys, interviews, and observations, with analysis conducted using both quantitative and qualitative methods. The findings indicate that SimLab significantly enhances various aspects of teaching proficiency, such as boosting self-confidence, improving the effectiveness of lesson delivery, engaging avatar students, interpreting avatar student body language and voice, providing constructive feedback, and fostering relationships with the avatars. However, the research also uncovers several challenges students face, including academic difficulties in adapting teaching methods to diverse student profiles, cultural obstacles related to the student's cultural adaptation, and technical challenges, such as unstable internet connections and limited technological facilities. The study concludes that while SimLab has substantial potential as a tool for preparing competent future educators, addressing these challenges is crucial for maximizing its effectiveness.